Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Answer:
(5, 6 )
Step-by-step explanation:
Given the 2 equations
2x - y = 4 → (1)
3x + y = 21 → (2)
Adding the 2 equations term by term will eliminate y
5x + 0 = 25
5x = 25 ( divide both sides by 5 )
x = 5
Substitute x = 5 into either of the 2 equations and solve for y
Substituting into (2)
3(5) + y = 21
15 + y = 21 ( subtract 15 from both sides )
y = 6
solution is (5, 6 )
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.